KCP Perspectives 3(1) - World Bank (World Bank, Washington, DC, 2015)
This newsletter includes the following headings: learning from the experiments that didn t happen: matching grant programs in Africa; message from the editor; and the worldwide governance indicators: synthesizing perceptions of governance quality across countries and over time.